Detection, Characterization, and Inhibition of FGFR–TACC Fusions in IDH Wild-type Glioma - Di Stefano, Anna Luisa; Fucci, Alessandra; Frattini, Veronique; Labussiere, Marianne; Mokhtari, Karima; Zoppoli, Pietro; Marie, Yannick; Bruno, Aurelie; Boisselier, Blandine; Giry, Marine; Savatovsky, Julien; Touat, Mehdi; et al. (Clinical cancer research, 2015)
Purpose: Oncogenic fusions consisting of fibroblast growth factor receptor (FGFR) and TACC are present in a subgroup of glioblastoma (GBM) and other human cancers and have been proposed as new therapeutic targets. We analyzed frequency and molecular features of FGFR–TACC fusions and explored the therapeutic efficacy of inhibiting FGFR kinase in GBM and grade II and III glioma. Experimental Design: Overall, 795 gliomas (584 GBM, 85 grades II and III with wild-type and 126 with IDH1/2 mutation) were screened for FGFR–TACC breakpoints and associated molecular profile. We also analyzed expression of the FGFR3 and TACC3 components of the fusions. The effects of the specific FGFR inhibitor JNJ-42756493 for FGFR3–TACC3–positive glioma were determined in preclinical experiments. Two patients with advanced FGFR3–TACC3–positive GBM received JNJ-42756493 and were assessed for therapeutic response. Results: Three of 85 IDH1/2 wild-type (3.5%) but none of 126 IDH1/2-mutant grade II and III gliomas harbored FGFR3–TACC3 fusions. FGFR–TACC rearrangements were present in 17 of 584 GBM (2.9%). FGFR3–TACC3 fusions were associated with strong and homogeneous FGFR3 immunostaining. They are mutually exclusive with IDH1/2 mutations and EGFR amplification, whereas they co-occur with CDK4 amplification. JNJ-42756493 inhibited growth of glioma cells harboring FGFR3–TACC3 in vitro and in vivo. The two patients with FGFR3–TACC3 rearrangements who received JNJ-42756493 manifested clinical improvement with stable disease and minor response, respectively. Conclusions: RT-PCR sequencing is a sensitive and specific method to identify FGFR–TACC–positive patients. FGFR3–TACC3 fusions are associated with uniform intratumor expression of the fusion protein. The clinical response observed in the FGFR3–TACC3–positive patients treated with an FGFR inhibitor supports clinical studies of FGFR inhibition in FGFR–TACC–positive patients. Clin Cancer Res; 21(14); 3307–17. ©2015 AACR. See related commentary by Ahluwalia and Rich, p. 3105